2022
DOI: 10.3390/plants11040477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytoplasma Associated with Sesame Phyllody on Ultrastructural Modification, Physio-Biochemical Traits, Productivity and Oil Quality

Abstract: Phytoplasmas are obligate cell-wall-less plant pathogenic bacteria that infect many economically important crops, causing considerable yield losses worldwide. Very little information is known about phytoplasma–host plant interaction mechanisms and their influence on sesame yield and oil quality. Therefore, our aim was to explore the ultrastructural and agro-physio-biochemical responses of sesame plants and their effects on sesame productivity and oil quality in response to phytoplasma infection. Sesame leaf sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…Such downregulated mechanisms of porphyrin and chlorophyll gene expression together with the enhancement of chlorophyllase activity in leaves of SCWL sugarcane evidently explain the symptoms of leaf chlorosis and low chlorophyll content caused by SCWL phytoplasma. The findings agree with the growth limitation of phytoplasma-infected sesame plants where photosynthetic rates were reduced due to the depletion of chlorophyll content, photosystem II photoprotection, and photosynthetic capacity [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 84%
“…Such downregulated mechanisms of porphyrin and chlorophyll gene expression together with the enhancement of chlorophyllase activity in leaves of SCWL sugarcane evidently explain the symptoms of leaf chlorosis and low chlorophyll content caused by SCWL phytoplasma. The findings agree with the growth limitation of phytoplasma-infected sesame plants where photosynthetic rates were reduced due to the depletion of chlorophyll content, photosystem II photoprotection, and photosynthetic capacity [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 84%
“…Currently, phytoplasmas are among the most dangerous plant diseases that harm economically essential crops (Bertaccini, 2021;Ahmed et al, 2021;Hemmati et al, 2021). Despite being a sign of the phytoplasma disease, which is prevalent in the Mediterranean region (Cagirgan et al, 2014), it is also a recent phytoplasma-disease symptom that appeared in Fayoum Governorate.…”
Section: Resultsmentioning
confidence: 99%
“…Sesame ( Sesamum indicum L.) is an important oil plant species with nutritious, medicinal, and edible uses [ 1 ]. One study suggested that globally, the total annual consumption of sesame as food and oil accounts for about 35% and 65%, respectively [ 2 ].…”
Section: Introductionmentioning
confidence: 99%